A novel lidocaine-chitosan-barium titanate microemulsion gel for prolonged local anesthesia: An in vitro study - Qiao, Xiaoru; Li, Ling (Archives of Biological Sciences, 2024)
Paper description: A new formulation of lidocaine microemulsions containing chitosan and BaTiO3 nanoparticles was developed for delivering lidocaine through the skin to achieve prolonged topical anesthesia. The lidocaine/chitosan/BaTiO3 microemulsion exhibited a nanometer size range of 7-30 nm with a narrow particle size distribution. The inclusion of BaTiO3 nanoparticles achieved over 84% drug release within 24 h, compared to 52% for the lidocaine/chitosan formulation without BaTiO3. At the concentrations tested, the lidocaine-loaded chitosan and lidocaine-loaded chitosan with BaTiO3 microemulsion gel showed a moderate effect on cellular viability, providing a non-toxic environment Abstract: This study investigated the efficacy of a novel lidocaine-chitosan-barium titanate microemulsion gel for prolonged local anesthesia. The lidocaine microemulsion comprised 5% (w/w) lidocaine, linoleic acid (LA), chitosan, barium titanate (BaTiO3), Cremophor RH40, Tween 20, and water. Dynamic light scattering was utilized to analyze the particle size of the prepared microemulsions. The optimized microemulsion was transformed into a microemulsion gel to extend the duration of the microemulsion when administered to specific areas. Virgin oil was used as an auxiliary oil to increase the microemulsion area, allowing for a reduced amount of surfactant. In vitro analysis was conducted to evaluate the release of lidocaine from the microemulsion. The lidocaine/chitosan/BaTiO3 ranged in size from 7-30 nm, displaying a narrow particle size distribution. The polydispersity index (PDI) value was 0.989. Lidocaine/chitosan with BaTiO3 nanoparticles as a carrier achieved over 84% drug release, whereas the lidocaine/chitosan without the BaTiO3 nanoparticles only reached 52% cumulative release. At the concentrations used, the lidocaine-loaded chitosan and lidocaine-loaded chitosan with BaTiO3 showed a moderate effect on cellular viability. In conclusion, a new formulation of lidocaine microemulsions containing chitosan and BaTiO3 was developed and utilized to deliver lidocaine through the skin to achieve topical anesthesia.